PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) OLEH PT INDAH KIAT PULP AND PAPER TBK. PERAWANG - Ikhvaldi Okta Rajiv; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Micro, Small and Medium Enterprises (MSMEs) itself is the development of four main economic activities which are the driving forces for Indonesia's development, namely: Manufacturing Industry, Agribusiness, Marine Business and Human Resources. In addition, MSMEs can also be interpreted as the development of reliable areas to accelerate economic recovery to accommodate priority programs and development of various sectors and potentials. Meanwhile, small businesses are an increase in various community empowerment efforts. The purpose of this research is to find out how to empower MSMEs PT. Indah Kiat Pulp and Paper Tbk. Perawang, as well as what are the supporting factors for UMKM PT. Indah Kiat Pulp and Paper Tbk. Perawang. This research uses qualitative research with a case study approach, which is descriptive analysis. The qualitative research process involves important efforts, such as asking questions and proposing procedures, gathering specific data from participants, analyzing data inductively from specific themes to general themes, and interpreting the meaning of the data. The results of this study indicate that: first, community empowerment through the PT. UMKM program. Indah Kiat Pulp and Paper Tbk. Perawang shows pretty good results, this can be seen from the changes felt by the community, especially as evidenced by the increase in community economic results. Second, the supporting factors for the empowerment of MSMEs PT. Indah Kiat Perawang is the existence of stages which are carried out sequentially, namely, the stages of awareness, capacitance and awareness. Keywords: Community empowerment, UMKM Program